Thermo-Hydraulic Performance of a Heat Exchanger Tube with Inserted Curved-Wing Tape Vortex Generators - Koolnapadol, Narin; Promvonge, Pongjet; Promthaisong, Pitak; Hoonpong, Panuwat; Khanoknaiyakarn, Chitakorn; Gururatana, Suabsakul; Skullong, Sompol (My University, 2024)
In the current study, thermal patterns and flow resistance in a heat exchange tube equipped with a curved-wing tape (CWT) vortex generator were experimentally analyzed to boost performance. A range of Reynolds numbers (Re) from 4130 to 25,370 was utilized in the experiment. The curved wings were arranged in forward array patterns for pitch length ratios (P/D = PR = 2.5, 2, and 1.5) and three wing attack angles (α = 10°, 20°, and 30°). The friction factor, f, and the Nusselt number, Nu, were utilized to quantify the pressure loss and heat transmission caused by the CWT insertion. The measured data reveal that utilizing the CWT resulted in a roughly 2.55-4.37 times greater increase in Nu than the smooth tube, whereas the rise in f is approximately 7.36-46.9 times. Raising the α value causes the Nu and f to trend upward, but increasing PR causes them to trend downward. The CWT's maximal thermal performance is approximately 1.58 at α = 10o and PR = 1.5. Correlations for f and Nu in the functional form of the CWT parameters have also been established.
Keywords: Curved-wing tape; Heat exchanger; Heat transfer; Vortex generator